Best Practice Recommendations for Dysphagia Management in Stroke Patients: A Consensus from a Portuguese Expert Panel - Isabel de Jesus Oliveira; Germano Rodrigues Couto; Rosa Vilares Santos; Ana Maria Campolargo; Cláudia Lima; Pedro Lopes Ferreira (Karger Publishers, 2022)
Dysphagia is frequent after stroke, and it increases the risk of respiratory infection, dehydration and malnutrition, resulting in worse outcomes. Different clinical guidelines present recommendations for the assessment and management of dysphagia in stroke patients in a scattered way. These best practice recommendations address seven clinical questions on the assessment and management of dysphagia in stroke patients, gathering the best-updated evidence. A systematic literature review using the PICO strategy was performed. The recommendations draft was then appraised by a multidisciplinary panel of experts (nutritionists, physiatrists, speech-language pathologists and rehabilitation nurses) in a total of 3 Delphi rounds. A minimum of 80% consensus was established, and the final version offers a total of 21 recommendations for use in clinical practice for stroke patients. These clinical recommendations are an overview of the most recent evidence combined with experts' consensus and translated into clinically relevant statements. In implementing recommendations at the local level, health professionals should identify facilitators and barriers to evidence-based practice within their contexts and determine the best strategies to address local needs. Where the change is needed, initial and continuing training on all recommendations is essential and relevant.